Pengaruh Game Super Sus Terhadap Pemerolehan Aspek Sintaksis Pada Anak Usia 9 Tahun - Amalia, Marisa Nurril; Putra, Dona Aji Karunia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this journal article research is to describe the forms of acquisition of syntactic aspects due to online games in children aged 9 years. his study used descriptive qualitative method. The subject in this study was a 9 year old child named Bima. The data in this study is in the form of qualitative data. The data collection for this research was carried out using notetaking techniques, interviewing 9-year-old children in their home environment who play online games. The results of the study show that the child is able to say declarative, imperative and interactive sentences.